An Evaluation Of Rural Internship Training Programme - Taneja D.K; Bhatia M.S; Sahgal K; Bansal A.K (Wolters Kluwer Medknow Publications, 1992)
An evaluation of two months rural internship training programme at the two medical colleges of Delhi revealed that posting did not help in improving the capacity of interns to deal with common illnesses and provide preventive maternal care. Intems could not improve as providers of primary health care in common emergencies. Though they significantly improved their knowledge relating to immunization programme, it was far from satisfactory. Lack of adequate facilities for training, absence of well formulated training programmes and lack of interest on the part interns themselves may be some of the underlying factors.